2004
DOI: 10.1210/jc.2003-032056
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Production of Plasma and Very-Low-Density Lipoprotein (VLDL) Apolipoprotein C-III Is Strongly Related to the Concentration and Level of Production of VLDL Triglyceride in Male Subjects with Different Body Weights and Levels of Insulin Sensitivity

Abstract: Overweight individuals with reduced insulin sensitivity often have mild to moderate hypertriglyceridemia. To investigate the role of apolipoprotein (apo)C-III metabolism in the etiology of hypertriglyceridemia in these individuals, we investigated 10 male subjects with different body weights (body mass index, 24-34 kg/m(2)) and insulin sensitivity (homeostasis model assessment, 4.7-35.0). Total plasma and very-low-density lipoprotein (VLDL) apoC-III kinetics, as well as VLDL triglyceride (TG) and VLDL apoB kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
102
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(121 citation statements)
references
References 58 publications
15
102
1
3
Order By: Relevance
“…No significant correlation was found between plasma apoC-III PR and VLDL apoB-100 FCR, which was rather surprising considering that apoC-III inhibits LPL activity and clearance of TG-rich lipoproteins (Wang et al, 1985;Windler and Havel, 1985). The inverse correlation between VLDL or plasma apoC-III PR and VLDL apoB-100 FCR has been observed in some (Chan et al, 2006) but not all studies (Cohn et al, 2004a). Reasons for these diverging results include differences in subjects' characteristics, in the kinetic study protocol, in the sample size and in the experimental design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant correlation was found between plasma apoC-III PR and VLDL apoB-100 FCR, which was rather surprising considering that apoC-III inhibits LPL activity and clearance of TG-rich lipoproteins (Wang et al, 1985;Windler and Havel, 1985). The inverse correlation between VLDL or plasma apoC-III PR and VLDL apoB-100 FCR has been observed in some (Chan et al, 2006) but not all studies (Cohn et al, 2004a). Reasons for these diverging results include differences in subjects' characteristics, in the kinetic study protocol, in the sample size and in the experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…Recent kinetic studies reported a close relationship between plasma or VLDL apoC-III and VLDL apoB kinetics in overweight or obese men (Chan et al, 2002;Cohn et al, 2004a). Chan et al (2002) reported that plasma concentrations of apoC-III were positively associated with VLDL apoB PR and inversely associated with VLDL apoB FCR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the effect of treatment with pioglitazone in a group of eight type 2 diabetic patients has shown a decrease in apolipoprotein C-III levels, although this is not thought to be mediated through the PPAR-γ receptor [36]. Some influence of insulin resistance on C-III levels can be inferred from the finding that its concentration in plasma correlates strongly with the level of production and concentration of VLDL triglyceride and also with the HOMA score of insulin sensitivity [37]. Taking these findings together, it remains possible that attenuated lipolysis by LPL of chylomicrons and other triglyceride-rich lipoproteins is the mechanism that explains delayed disposal of dietary lipid, even though the LPL activities measured under optimal conditions were equal in the control subjects and the diabetic patients regardless of the treatment regime.…”
Section: Discussionmentioning
confidence: 99%
“…19 Third, several studies have shown that apoC-III inhibits receptor-mediated uptake of TRL by the liver. 21,22 Kinetic studies using tracer methodology have confirmed that VLDL-apoC-III is overproduced in overweight insulin-resistant subjects, 15 in hypertriglyceridemic subjects compared with controls, 53 and in centrally, obese men compared with controls. 54 Increased plasma concentrations of apoC-III are associated with impaired VLDL1 clearance in obese insulin-resistant men 55 and VLDLapoC-III clearance is reduced in centrally obese men compared with controls.…”
Section: Discussionmentioning
confidence: 95%
“…12 In hypertriglyceridemic subjects, apoC-III levels proportion bound to TRL are increased in the fasting state. 13 Plasma apoC-III concentration is strongly correlated with plasma triglyceride (TG) concentration 14,15 and is increased in insulin-resistant states (overweight or obesity 15 and type II diabetes 16,17 ). Elevated apoC-III has been postulated to contribute to the atherogenic dyslipidemia by the impairment of TRL and HDL metabolism including increased VLDL production and secretion, 18 disturbance of TRL clearance by inhibiting LPL 19 or hepatic lipase, 20 and interfering with TRL and their remnant binding to hepatic lipoprotein receptors.…”
Section: Introductionmentioning
confidence: 99%